2015
DOI: 10.1039/c5lc00947b
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic devices to enrich and isolate circulating tumor cells

Abstract: Given the potential clinical impact of circulating tumor cells (CTCs) in blood as a clinical biomarker for diagnosis and prognosis of various cancers, a myriad of detection methods for CTCs have been recently introduced. Among those, a series of microfluidic devices are particularly promising as these uniquely offer micro-scale analytical systems that are highlighted by low consumption of samples and reagents, high flexibility to accommodate other cutting-edge technologies, precise and well-defined flow behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 81 publications
0
48
0
1
Order By: Relevance
“…Isolation of CTCs from blood is critical owing to the fact that metastatic CTCs may hold different genomic and phenotypic properties which may provide insights for prognosis and effective treatment. Focusing biological particles and cells using microfluidic systems have been implemented as an efficient CTCs enumeration and enrichment method for clinical diagnostics applications89. Focusing particles and cells into a narrow stream is a requirement for these emerging applications and for understanding the underlying physics of particle/cell focusing in microfluidics10.…”
mentioning
confidence: 99%
“…Isolation of CTCs from blood is critical owing to the fact that metastatic CTCs may hold different genomic and phenotypic properties which may provide insights for prognosis and effective treatment. Focusing biological particles and cells using microfluidic systems have been implemented as an efficient CTCs enumeration and enrichment method for clinical diagnostics applications89. Focusing particles and cells into a narrow stream is a requirement for these emerging applications and for understanding the underlying physics of particle/cell focusing in microfluidics10.…”
mentioning
confidence: 99%
“…Still the CellSearch system remains the gold standard for CTC enumeration and has set the bar quite high (Bidard et al, 2014;Mehra et al, 2015). Over the years several alternative technologies have been developed reviewed extensively elsewhere (Alix-Panabi eres and Pantel, 2014; Barradas and Terstappen, 2013;Krebs et al, 2014;Myung and Hong, 2015) and demonstrated to detect CTC both by targeting EpCAM and not targeting EpCAM but using Figure 6 e What is and what isn't a CTC. Left part of the figure shows seven areas with objects in which the CellTracks software identified cytokeratin (CK) as well as DNA staining.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has been conducted on devices fabricated using the classical soft lithography process for fast prototyping. This process, however, has some drawbacks regarding reproducibility and scalability . Manual alignment of a cast polydimethylsiloxane (PDMS) channel structure to electrodes defined on a glass substrate typically requires a high level of manual skill .…”
Section: Critical Challenges In Dep Enrichment Of Ctcsmentioning
confidence: 99%
“…Manual alignment of a cast polydimethylsiloxane (PDMS) channel structure to electrodes defined on a glass substrate typically requires a high level of manual skill . Non‐specific binding of cells to the PDMS structure is another possible impediment to the yield and the general functionality of a device . On the other hand, glass‐ and silicon‐based fabrication techniques have the advantages of robustness and scalability, although the fabrication process requires advanced knowledge and skills, and specialized cleanroom equipment.…”
Section: Critical Challenges In Dep Enrichment Of Ctcsmentioning
confidence: 99%